Traktörlerde Egzoz Gürültüsü - Öztürk, Hakan (Fen Bilimleri Enstitüsü, 2015)
Bu çalışmada, taşıtların gürültü kaynakları incelenmiş ve egzoz gürültüsünün toplam taşıt gürültüsünde dominant karaktere sahip olduğu vurgulanmıştır. Egzoz prosesi incelenerek gürültü oluşumu açıklanmıştır. Akustik filtreler teorisi ile hesaplanan ve ölçümlerle karşılaştırılan gürültü analizlerinden yararlanarak susturucuların tasarım parametreleri incelenmiş ve bütün değişkenlerin gürültüye etkileri değerlendirilmiştir. Bu verilere dayanarak traktörlerde kullanılan bir susturucu için akustik iyileştirme önerileri sunulmuştur. İmal edilen prototip susturucu ile mevcut susturucunun karşılaştırmalı testlerle gürültü seviyeleri ölçülmüş ve iyileştirme miktarı saptanmıştır. Egzoz sisteminde yapılacak akustik iyileştirmeler genellikle egzoz gaz akışına uygulanacak dirençler yardımıyla olmaktadır.Yaratılacak ilave dirençler, motor performansını olumsuz etkileyen geri basınç miktarını arttıracaktır. Yapılan testlerde geri basınç miktarları da ölçülmüş, önerilen susturucunun motor spesifikasyonlarında belirtilen sınır değerleri aşmadığı gözlenmiştir.

In this study, the noise sources of the vehicles are examined. Exhaust system has the dominant noise characteristics on the total noise of the vehicle. Exhaust process and noise are explained. According to the comparison results of theory of exhaust mufflers calculations and measurements, the design parameters of silencers are examined. The effects of all these variables on the noise are considered. As a result of this data, acoustic development and suggestions are presented and also calculated for a silencer used on a tractor. One of the suggested muffler is produced. The noise of prototype muffler is measured in comparison with the current one on the tractor and the improvement is determined. The noise control methods in reactive mufflers are mostly based on resisting of mean flow of exhaust gas. Creating resistance on the way of exhaust gas flow usually increases the back pressure of muffler which has negative effects on the engine performance. Back pressure values are measured at the same time with the noise. It is seen that a little increase is provided in the transmission lost and the expected increased back pressure was in the limits of engine specifications.
Exhaust Noise Of Agricultural Tractors
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2001
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2001
Keywords: Egzoz; Susturucu; Gürültü; Akustik; Traktör; Exhaust; Muffler/Silencer; Noise; Acoustic; Tractor